ANALISIS PENDAPATAN USAHA BUDIDAYA UDANG VANAME DI KECAMATAN BAYAN KABUPATEN LOMBOK UTARA - Widiyanti, Ni Made Nike Zeamita; Husni, Syarif; Yusuf, M.; Agustina, Shelly Sylvia; Nursan, Muhammad (JURNAL AGRIMANSION, 2025)
Vaname shrimp produced in West Nusa Southeast Province is one of the vaname shrimp with high economic value. This vaname shrimp is not only sold in the local market, but also to the international market. One of the centers of vaname shrimp farming is in Bayan Subdistrict, North Lombok Regency. Vaname shrimp farming in Bayan Subdistrict is mostly done by women as an effort to increase their household income. The income level of this vaname shrimp farming business greatly affects the survival of this vaname shrimp entrepreneur. Based on this, the purpose of this study was to analyze the income of vaname shrimp farming business in Bayan District, North Lombok Regency. The research method was conducted with quantitative methods. The number of respondents was determined as many as 31 respondents through the slovin calculation technique with a 10% error rate. The results of the study showed the total costs incurred amounted to Rp 14,907,421 per year. While the total revenue obtained was Rp 28,459,274 per year. so that the net income earned was 13,551,853 per year.